2017
DOI: 10.3171/2016.5.jns16493
|View full text |Cite
|
Sign up to set email alerts
|

Endoscope-assisted transsphenoidal puncture of the cavernous sinus for embolization of carotid-cavernous fistula in a neurosurgical hybrid operating suite

Abstract: Endovascular embolization is the treatment of choice for carotid-cavernous fistulas (CCFs), but failure to catheterize the cavernous sinus may occur as a result of vessel tortuosity, hypoplasia, or stenosis. In addition to conventional transvenous or transarterial routes, alternative approaches should be considered. The authors present a case in which a straightforward route to the CCF was accessed via transsphenoidal puncture of the cavernous sinus in a neurosurgical hybrid operating suite. This 82-year-old m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Tang et al. [10] reported an indirect CCF treated using endoscope-assisted transsphenoidal puncture of CS for embolization. However, because of the invasiveness and the need for a hybrid operating room, we elected to navigate microcatheter through the retromandibular vein, maxillary vein, pterygoid plexus, and emissary vein into the CS for embolization.…”
Section: Discussionmentioning
confidence: 99%
“…Tang et al. [10] reported an indirect CCF treated using endoscope-assisted transsphenoidal puncture of CS for embolization. However, because of the invasiveness and the need for a hybrid operating room, we elected to navigate microcatheter through the retromandibular vein, maxillary vein, pterygoid plexus, and emissary vein into the CS for embolization.…”
Section: Discussionmentioning
confidence: 99%
“…the angular vein, are present, making transfemoral/-venous approaches difficult in many cases. 3,4) Previously, a microcatheter was inserted into the angular vein through a minor incision, but this was relatively invasive, being a disadvantage. Furthermore, an approximately 10-mm incision was required in many cases, being esthetically disadvantageous.…”
Section: Discussionmentioning
confidence: 99%
“…1,2) Tang reported that neurological complications were observed in 4 of 20 patients in whom TVE was performed via the IPS with thrombosis-related occlusion, and the mean IPS approach time was 111 minutes. 3) In many patients with IPS occlusion, the SOV functions as a main drainage vein. The SOV itself is markedly swollen, but tortuosity/stenosis of the peripheral veins, such as sulcus on the body surface, and the mean vascular diameter is reportedly 2.2 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Ghosh et al described a patient who underwent image-guided burr hole placement to allow catheterization of the Sylvian vein and subsequently access the CS and then embolize the patient’s CCF [ 31 ]. Endoscopic-assisted transsphenoidal access to the CS for CCF treatment has also been described [ 32 ]. These approaches, and more, highlight the creativity of the endovascular surgeon and the multitude of options available.…”
Section: Discussionmentioning
confidence: 99%